Pengujian Kekerasan Dan Pengamatan Foto Makro Automatic Surface Treatment Rel Dengan Variasi Jarak Torch Pemanas Dan Nozzle Pendingin - Wahjono, Hari Boedi; Permana, Adinda Cahya Permana Cahya (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2021)
The prototype automatic surface treatment whose specifications include using an oxy-acetylene welding kit, with a 12V/24V DC motor, 12V battery supply, and a 12V water pump still does not have technical data on the increase in hardness produced. This study aims to compare the calculation of the value of the R.54 rail hardness between raw materials and materials that undergo automatic surface treatment. In this study, the testing method used is the Brinell test method. In this study, variations of the distance between the heater and cooler were carried out with a distance of 100mm, 130mm, and 160mm. The results of the tests that have been carried out, variations with a distance of 160mm resulted in the highest increase in hardness values. It increased by 8.9355 BHN, while in the 130mm variation it was slightly lower at 8.2581 BHN, and in the 100mm variation the hardness value only increased by 6.9892 BHN. With this, the lifetime of the rail will also increase, it is assumed that by calculating the age of the rail on the Indonesian Railway Polytechnic cross, surface treatment can increase the life of the rail. Keywords: Automatic Surface Treatment, Distance, Hardness, Rail Life.